Screen-printed Carbon Electrode from Coconut Shell Activated Carbon Modified with Ferrocene for Cobalt Detection - Muhammad Farhan; Eddy Heraldy; Abu Masykur; Muhammad A. Munir; Fitria Rahmawati (ALCHEMY Jurnal Penelitian Kimia, 2024)
This research aims to fabricate a screen-printed carbon electrode (SPCE) from coconut shell charcoal. The charcoal was activated with NaOH to produce activated carbon (Ac). It was mixed with acetylene black (AB) and poly (vinylidene) Fluoride (PVDF) at the mass ratio of 7:2:1 for the Ac, AB, and PVDF, respectively, followed by a dispersing with N-Methyl-2-Pyrrolidinone (NMP) producing carbon slurry that was painted on a SPCE template. To increase electrochemical sensitivity, ferrocene, Fc was dropped onto the working electrode part at 10%, 20%, and 30% of the total SPCE mass. The results show that Ac is amorphous with a porous chip-like morphology containing 61.7% carbon. Ac shows vibrations of O–H, C=O, C=C, C–O, and Si–O with surface area and average pore size of 154.612 m2 g-1 and 1.42 nm, respectively. The cyclic voltammetry analysis found that 10% Fc on SPCE provides the highest current density compared to 20% and 30%. Meanwhile, the 2 mV s-1 scanning rate reveals a more defined anodic and cathodic peak than 3 mV s-1 and 5 mV s‑1. Furthermore, the SPCE with 10% Fc shows a good sensitivity to Co (II) ions, proven by a low detection limit (LoD) of 0.224 mmol L-1